Targeting Diabetes-Associated Neurodegeneration: Neuroprotective Role of a Novel Antidiabetic Formulation - Tripathi, Rituraj; Omray, Lavakesh Kumar; Gupta, Naveen; Patel, Ganesh Prasad; Agrawal, Hemant (Journal of Neonatal Surgery, 2025)
Diabetes mellitus is increasingly recognized not only as a metabolic disorder but also as a significant contributor to neurodegenerative changes in the central nervous system. Chronic hyperglycemia, insulin resistance, and associated metabolic disturbances have been closely linked with cognitive decline and an elevated risk of neurodegenerative conditions such as Alzheimer’s disease. The concept of diabetes-associated neurodegeneration highlights the complex interplay between metabolic dysfunction and neuronal damage, involving mechanisms such as oxidative stress, neuroinflammation, mitochondrial impairment, and the accumulation of toxic protein aggregates. Despite advancements in antidiabetic therapies, conventional treatments primarily focus on glycemic control and often fail to address underlying neuronal damage. This has led to growing interest in the development of novel antidiabetic formulations with additional neuroprotective properties. Such formulations aim to target multiple pathological pathways simultaneously, offering improved therapeutic outcomes by reducing oxidative damage, modulating inflammatory responses, and enhancing neuronal survival. This review provides a comprehensive overview of the molecular mechanisms linking diabetes to neurodegeneration and critically evaluates the neuroprotective potential of emerging antidiabetic formulations. Furthermore, it highlights recent advances in drug delivery strategies and discusses current challenges and future perspectives in this evolving field. Understanding these interconnected mechanisms may pave the way for more effective therapeutic interventions aimed at preserving cognitive function in diabetic patients